Heart rate reactivity, recovery, and endurance of the incremental shuttle walk test in patients prone to heart failure - Fang‐Fei Wei; Beatrice Mariottoni; De‐Wei An; Pierpaolo Pellicori; Yu‐Ling Yu; Job A. J. Verdonschot; Chen Liu; Fozia Z. Ahmed; Johannes Petutschnigg; Patrick Rossignol; Stephane Heymans; Joe Cuthbert; et al. (ESC Heart Failure)
Abstract Aims Few randomized trials assessed the changes over time in the chronotropic heart rate (HR) reactivity (CHR), HR recovery (HRR) and exercise endurance (EE) in response to the incremental shuttle walk test (ISWT). We addressed this issue by analysing the open HOMAGE (Heart OMics in Aging) trial. Methods In HOMAGE, 527 patients prone to heart failure were randomized to usual treatment with or without spironolactone (25–50 mg/day). The current sub‐study included 113 controls and 114 patients assigned spironolactone (~70% on beta‐blockers), who all completed the ISWT at baseline and at Months 1 and 9. Within‐group changes over time (follow‐up minus baseline) and between‐group differences at each time point (spironolactone minus control) were analysed by repeated measures ANOVA, unadjusted or adjusted for sex, age and body mass index, and additionally for baseline for testing 1 and 9 month data. Results Irrespective of randomization, the resting HR and CHR did not change from baseline to follow‐up, with the exception of a small decrease in the HR immediately post‐exercise (−3.11 b.p.m.) in controls at Month 9. In within‐group analyses, HR decline over the 5 min post‐exercise followed a slightly lower course at the 1 month visit in controls and at the 9 month visits in both groups, but not at the 1 month visit in the spironolactone group. Compared with baseline, EE increased by two to three shuttles at Months 1 and 9 in the spironolactone group but remained unchanged in the control group. In the between‐group analyses, irrespective of adjustment, there were no HR differences at any time point from rest up to 5 min post‐exercise or in EE. Subgroup analyses by sex or categorized by the medians of age, left ventricular ejection fraction or glomerular filtration rate were confirmatory. Combining baseline and Months 1 and 9 data in both treatment groups, the resting HR, CHR and HRR at 1 and 5 min averaged 61.5, 20.0, 9.07 and 13.8 b.p.m. and EE 48.3 shuttles. Conclusions Spironolactone on top of usual treatment compared with usual treatment alone did not change resting HR, CHR, HRR and EE in response to ISWT. Beta‐blockade might have concealed the effects of spironolactone. The current findings demonstrate that the ISWT, already used in a wide variety of pathological conditions, is a practical instrument to measure symptom‐limited exercise capacity in patients prone to developing heart failure because of coronary heart disease.